Temporal sutureless vitrectomy in infectious scleritis with retinal detachment - Khanduja, S; Venkatesh, P; Garg, S; Sinha, S (Nepalese Journal of Ophthalmology, 2013)
Nepal J Ophthalmol 2013; 5(9):138 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7844